The Treatment Outcomes of Olfactory Neuroblastoma Patients With Frontal Lobe Invasion - Wang, Jie; Wang, Li; He, Huanyu; Li, Yi; Song, Xinmao (Frontiers in Oncology, 2021)
Background To investigate whether frontal lobe invasion (FLI) was an unfavorable prognostic factor in patients with olfactory neuroblastoma (ONB), and to explore the optimal treatment strategy for ONB patients with FLI. Methods Some 37 patients with FLI were retrospectively studied, and 74 well-matched patients without FLI were enrolled as the control group. The long-term survivals were compared between the two groups. Results No significant differences were found between the two groups in overall survival (OS), progression-free survival (PFS), locoregional failure-free survival (LRFS), and distant metastasis-free survival (DMFS) (all p >0.05). Multivariate analyses showed that FLI wasn’t an independent predictor for OS (HR = 1.100, 95% CI = 0.437–2.772, p = 0.840). Among the 37 patients with FLI, patients who received surgery combined with chemo-/radiotherapy showed better OS (89.4% vs. 53.6%, p = 0.001) and PFS (87.8% vs. 53.6%, p = 0.001) compared with those who didn’t undergo surgery. Conclusions FLI wasn’t a poor prognostic factor for ONB patients. Endoscopic resection combined with radiotherapy was an effective therapeutic method for ONB patients with FLI.